Telling Phaedrus' fables to children. A cruel language? A linguistic analysis in Italian books - Alberto Regagliolo (The Journal of Classics Teaching)
Teaching classical culture to children can be done through literature and Phaedrus' fables. There are several books on the market that can be used to introduce Phaedrus' fables to children. However, in order to be suitable, the books should follow some requirements of appropriateness related to the use of the language and the values to be shared, among others. In this study, through the analysis of 12 Italian books on Phaedrus' fables for children, it will be analysed how the death of an animal is described through the use of verbs and structures. The research aims at making observations on how some books for children represent cruelty and the adoption of certain linguistic structures. The analysis shows, in the first place, that the authors never eliminate the death/killing of the animal; secondly, the verbs and expressions used are varied but, in most cases, cruel, and direct without making the death softer.